Integrating local wisdom into learning in school’s curriculum: A bibliometric analysis - K. Khusyairin; Udin Saefudin Sa'ud; S. Sururi; Nani Hartini (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2024)
This study presents a bibliometric analysis of research on integrating local wisdom into school learning, providing a comprehensive overview of scholarly developments from 2010 to 2024. Utilizing the Scopus database, the bibliometric method retrieved an initial 284 documents, refined to 145 after applying inclusion criteria. The analysis reveals a significant annual growth rate of 28.21 percent in publications, indicating a burgeoning interest in this field. Indonesia emerged as the leading contributor in the number of publications and citations; the most productive authors and the most cited documents also originated from Indonesia. Co-occurrence keyword analysis identified vital themes such as character education, the development of learning media, and the innovative use of technology—including mobile learning and augmented reality—to facilitate local wisdom integration. Despite the predominance of Indonesian research, international collaboration remains limited, highlighting opportunities for comparative studies and broader global engagement. The findings suggest integrating local wisdom into education enhances cultural preservation, student engagement, and moral development. Future research should explore technology's role in this integration, assess long-term educational outcomes, and encourage international partnerships to enrich the global discourse on culturally responsive education. AbstrakStudi ini menyajikan analisis bibliometrik penelitian tentang integrasi kearifan lokal ke dalam pembelajaran di sekolah, memberikan gambaran komprehensif tentang perkembangan ilmiah dari tahun 2010 hingga 2024. Dengan memanfaatkan basis data Scopus, metode bibliometrik awalnya memperoleh 284 dokumen, yang kemudian disaring menjadi 145 setelah menerapkan kriteria inklusi. Analisis menunjukkan tingkat pertumbuhan publikasi tahunan yang signifikan sebesar 28,21 persen, mengindikasikan minat yang semakin meningkat di bidang ini. Indonesia muncul sebagai kontributor terdepan dalam hal jumlah publikasi dan sitasi; penulis paling produktif dan dokumen yang paling banyak disitasi juga berasal dari Indonesia. Analisis ko-occurance kata kunci mengidentifikasi tema-tema kunci seperti pendidikan karakter, pengembangan media pembelajaran, dan penggunaan teknologi inovatif—termasuk pembelajaran mobile dan augmented reality—untuk memfasilitasi integrasi kearifan lokal. Meskipun penelitian Indonesia mendominasi, kolaborasi internasional masih terbatas, menyoroti peluang untuk studi komparatif dan keterlibatan global yang lebih luas. Temuan ini menunjukkan bahwa mengintegrasikan kearifan lokal ke dalam pendidikan meningkatkan pelestarian budaya, keterlibatan siswa, dan pengembangan moral. Penelitian selanjutnya harus mengeksplorasi peran teknologi dalam integrasi ini, menilai hasil pendidikan jangka panjang, dan mendorong kemitraan internasional untuk memperkaya diskursus global tentang pendidikan yang responsif secara budaya.Kata Kunci: bibliometrik; kearifan lokal; kurikulum; pembelajaran; sekolah